Ketersediaan Unsur Besi, Molibdenum, Aluminium dan C/N Total Pada Lahan Gambut Bekas Terbakar Berulang di Kabupaten Bengkalis - T. Abu Hanifah (Universitas Riau, 2019)
Land fire will be impact to the physical and chemical characteristics of soil that caused of decomposition proces. The different land fire frequency will be affect to different in the soil composition. To know how far that the composition is different so it need to do research about the contains of micro element such as Fe, Mo, Al available and ratio C/N in area Pakning Asal, Bengkalis Regency. The contains of Fe and C-organic was determined using Spectrophotometer UV-VIS, the contains of Mo and Al was determined using Atomic Absorbtion Spectrophotometer and the contain of N was determined by Kjeldahl method. Analysis result showed that contains of Fe, Mo, Al and ratio C/N in unburnt soil, once burned soil and several times burned (2 – 3 times in last 5 years) there were 14.1566 mg/Kg; 15.3151 mg/Kg and 5.7677 for Fe; 0,0548 mg/Kg, 0.1345 mg/Kg and 0.0830 mg/Kg for Mo; 12.5655 mg/Kg, 12.2220 mg/Kg and 8.9683 mg/Kg for Al and was increased 16.6855; 20.6787 and 25.5206 for ratio C/N.